Actinides filtering out in the demo-imitation separator with a magnetic field of a given configuration - Yuferov, V.B.; Katrechko, V.V.; Ilichova, V.O.; Khizhnyak, S.N. (Вопросы атомной науки и техники, 2022)
To simulate spent nuclear fuel (SNF) cleaning up from fission products, the concept of a demonstration-imitation separator (DIS) with a plasma rotating in crossed electric and magnetic fields is being clarified. The parameters of a magnetic system consisting of a combination of superconducting and water-cooled windings are presented. The features of plasma drift in a magnetic field of a given geometry are pointed. The estimation of energy consumption for the creation of a magnetic field of the separator, which is ~ 250 kW, has been carried out. A method for removing actinides from a plasma separator into an external container is proposed. Для моделювання очищення ВЯП від продуктів поділу відпрацьовується концепція демонстраційно імітаційного сепаратора з плазмою, що обертається в схрещених електричному та магнітному полях. Представлені параметри магнітної системи, яка складається з комбінації надпровідних обмоток й обмоток, що охолоджуються водою. Відзначено особливості дрейфу плазми в магнітному полі заданої геометрії. Проведена оцінка енергозатрат на створення магнітного поля сепаратора, яка складає ~ 250 кВт. Запропоновано спосіб виведення актиноїдів з плазмового сепаратора в зовнішній контейнер. Для моделирования очистки ОЯТ от продуктов деления отрабатывается концепция демонстрационно имитационного сепаратора с плазмой, вращающейся в скрещенных электрическом и магнитном полях. Представлены параметры магнитной системы, состоящей из комбинации сверхпроводящих и водоохлаждаемых обмоток. Отмечены особенности дрейфа плазмы в магнитном поле заданной геометрии. Проведена оценка энергозатрат на создание магнитного поля сепаратора, которая составляет ~ 250 кВт. Предложен способ выведения актиноидов из плазменного сепаратора во внешний контейнер.